Front teeth replacement with implant-supported crowns: A case report - K.K., Michael Josef; Hendrijantini, Nike; A, Maretaningtias Dwi; W, Wiwik Herawati (Indonesian Journal of Prosthodontic, 2021)
The use of dental implants to support fixed or removable restoration is widely used as treatment modality. The advantages are increased retention, chewing ability, and easy access to oral hygiene procedures. A missing tooth that needs to be replaced completely can be restored using an implant-supported crown. The aim of this study is to rehabilitate maxillary partial edentulous with implant supported crown. A 56-year-old female patient came to the clinic, wanted to replace partial edentulous after extraction of 11 and 21, needed fixed restoration in order to eat and chew well, and expected high aesthetic result as well. This patient had experienced using removable partial denture to replace her lost teeth . Patient wanted to have implant treatment with fixed restoration because she felt that her partial denture did not fit anymore, so the prosthodontic treatment option was using implant-supported crowns. Implant supported crown can be an option to replace partial edentulous.